1991
DOI: 10.1007/bf00210531
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins in osteoid osteoma

Abstract: Osteoid osteoma is a tumour of bone characterised by pain which is relieved by aspirin and nonsteroidal anti-inflammatory drugs. Very high levels of prostaglandins have been found in the lesion. In five patients with osteoid osteoma, prostaglandin E2 (PGE2) and prostacyclin (PGI2) synthesis in the nidus yielded 1155.6 +/- 496.5 (mean +/- SD) and 245.2 +/- 89.8 pg/mg respectively, values which are 33 and 26 times higher than in fragments of normal bone. The sclerotic bone around the nidus produced both prostagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 11 publications
3
54
0
6
Order By: Relevance
“…The patient may even move and cause a loss of position. The reaction subsequently normalizes when the lesion is completely destroyed and seems compatible with theories suggesting a neurogenic origin for the pain associated with an osteoid osteoma [18][19][20]. We routinely ask our anesthetist to look for this reaction because it is useful confirmation that we have entered a nidus.…”
Section: Physiologic Reaction To Radiofrequency Thermal Ablationsupporting
confidence: 63%
“…The patient may even move and cause a loss of position. The reaction subsequently normalizes when the lesion is completely destroyed and seems compatible with theories suggesting a neurogenic origin for the pain associated with an osteoid osteoma [18][19][20]. We routinely ask our anesthetist to look for this reaction because it is useful confirmation that we have entered a nidus.…”
Section: Physiologic Reaction To Radiofrequency Thermal Ablationsupporting
confidence: 63%
“…Later, Markley et al (12), Greco et al (13,14,28), and one of the authors of the present study (TH) (3) demonstrated an increase in PGE2 level in the nidus by radioimmunoassay (RIA) and immunohistochemical studies using anti-PGE2 antibodies. PG produced within the nidus has been proposed to be a mediator of synovitis in intraarticular OO (7,23,29).…”
Section: Discussionsupporting
confidence: 52%
“…Because Markley et al (12) and Greco et al (13,14) demonstrated a higher level of PGs in the nidus of OO, PGE2 has been suspected as a mediator that contributes to synovitis in the involved joint of intraarticular OO. As is well known, PGs are produced from phospholipids catalyzed by cytosolic phospholipase A2 (cPLA2) and cyclooxygenase (COX)-2 through arachidonic acid metabolism.…”
mentioning
confidence: 99%
“…Prostaglandins produced by the tumour result in a chronic inflammatory response in the surrounding tissues which is demonstrated by a periosteal reaction and synovitis. These regress spontaneously after removal of the nidus [9,17].…”
Section: Introductionmentioning
confidence: 99%